Chemical space is big. Really big. Issue 1 (5th January 2015) - Lowe, Derek
Abstract : You think it's a long way to the back of your screening libraries? That's peanuts to chemical space, says Derek Lowe. Abstract : Derek Lowe (@Dereklowe) is a medicinal chemist working on preclinical drug discovery in the US and blogs at In the pipeline: Web:http://pipeline.corante.com/